Securitization of Real Estate in Singapore - Patel, Nishkal (2007)
This dissertation investigates the various perspectives relating to securitization, aiming to give a comprehensive and complete understanding of the issues evolving around it. The study here focuses the benefits and drawbacks of securitization in Singapore. Asset backed securitization originated in the US in 1968 and subsequently attracted European countries. Knowing the importance of assets backed securities in the developed countries capital market, this dissertation looks into ways of establishing successful secondary markets for these asset backed securities in Singapore.